Sustainable development & environmental protection: the accounting practices of GHG emission in Malaysia - Namdar, Javad; Mohd Said, Ridzwana; Senik, Rosmila (2015)
Our study on the greenhouse gas (GHG) emission focused on the current state of art of Malaysian GHG emission accounting practices. Data was download through 36 companies’ website. All companies are listed company on the Main Market of Bursa Malaysia. A content analysis of annual reports carried out for the year 2012.